SIRPα on Mouse B1 Cells Restricts Lymphoid Tissue Migration and Natural Antibody Production - Franke, Katka; Pillai, Saravanan Y.; Hoogenboezem, Mark; Gijbels, Marion J. J.; Matlung, Hanke L.; Geissler, Judy; Olsman, Hugo; Pottgens, Chantal; van Gorp, Patrick J.; Ozsvar-Kozma, Maria; Saito, Yasuyuki; Matozaki, Takashi; et al. (Frontiers in Immunology, 2020)
The inhibitory immunoreceptor SIRP is expressed on myeloid and neuronal cells and interacts with the broadly expressed CD47. CD47-SIRP interactions form an innate immune checkpoint and its targeting has shown promising results in cancer patients. Here, we report expression of SIRP on B1 lymphocytes, a non-conventional subpopulation of murine B cells responsible for the production of natural antibodies. Mice defective in SIRP signaling (SIRPCYT mice) displayed an enhanced CD11b/CD18 integrin-dependent B1 cell migration from the peritoneal cavity to the spleen, local B1 cell accumulation, and enhanced circulating natural antibody levels, which was further amplified upon immunization with T-independent type 2 antigen. As natural antibodies are atheroprotective we investigated the involvement of SIRP signaling in atherosclerosis development. Bone marrow (SIRPCYT>LDLR-/-) chimaeric mice developed reduced atherosclerosis accompanied by increased natural antibody production. Collectively, our data identify SIRP as a unique B1 cell inhibitory receptor acting to control B1 cell migration, and imply SIRPas a potential therapeutic target in atherosclerosis.